2003
DOI: 10.1090/s0002-9947-03-03349-x
|View full text |Cite
|
Sign up to set email alerts
|

Automorphic forms and differentiability properties

Abstract: Abstract. We consider Fourier series given by a type of fractional integral of automorphic forms, and we study their local and global properties, especially differentiability and fractal dimension of the graph of their real and imaginary parts. In this way we can construct fractal objects and continuous non-differentiable functions associated with elliptic curves and theta functions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
20
0

Year Published

2004
2004
2017
2017

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 13 publications
(20 citation statements)
references
References 18 publications
0
20
0
Order By: Relevance
“…The conditions are met by certain series arising from modular forms. These and other related series has been treated by several authors in connection with fractal and multifractal analysis [Cha04], [HT91], [Jaf96], [MS04], [Ota10], [Pet13], [RC14]. We deal with them in Section 3 and we deduce that the spectra of singularities of fractional integrals of cusp forms have a discrete image, in this sense they are pure fractals.…”
Section: Introductionmentioning
confidence: 83%
See 1 more Smart Citation
“…The conditions are met by certain series arising from modular forms. These and other related series has been treated by several authors in connection with fractal and multifractal analysis [Cha04], [HT91], [Jaf96], [MS04], [Ota10], [Pet13], [RC14]. We deal with them in Section 3 and we deduce that the spectra of singularities of fractional integrals of cusp forms have a discrete image, in this sense they are pure fractals.…”
Section: Introductionmentioning
confidence: 83%
“…The proof of this result requires especial considerations when α − r/2 is a positive integer. In this case we need the following lemma that, in some sense, completes [Cha04] (cf. Corollary 2.1.1) including an extremal case.…”
Section: In Our Ranges This Givesmentioning
confidence: 99%
“…More recently several authors have shown interest on the global properties of R and allied functions (this interest was initially linked to wavelet methods [JM96], [HT91]). For instance, it is known that the (box counting) dimension of the graph of R is 5/4, in particular it is a fractal [Cha04], [CC99].…”
Section: Introductionmentioning
confidence: 99%
“…Basically R α is a fractional integral of the automorphic theta function θ(z) = ∞ n=−∞ e(n 2 z) and the local behavior of R α at a given x is determined by the convergents in the continued fraction of x and by the Fourier expansion of θ at the cusps (every rational number is equivalent to a cusp). This approach is developed in [Cha04] and [MS04] in a broader context.…”
Section: Introductionmentioning
confidence: 99%
“…The absolute value of φ(x) also oscillates rapidly, as is illustrated by figure 2. Near the origin |φ(x)| evidently displays fractal behavior -see figure 3.…”
Section: Introductionmentioning
confidence: 99%